2007
DOI: 10.1111/j.1540-8159.2007.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

The ICD Shock and Stress Management Program: A Randomized Trial of Psychosocial Treatment to Optimize Quality of Life in ICD Patients

Abstract: These results suggest that structured interventions for shocked ICD patients involving ICD education and cognitive-behavioral strategies can reduce psychological distress and improve quality of life, regardless of format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(129 citation statements)
references
References 34 publications
2
120
1
6
Order By: Relevance
“…Stress management interventions after an ICD shock were tested by Sears et al 167 One intervention consisted of a CBT stress management intervention delivered by psychologists over 6 weeks in 90-minute sessions, for a total of 9 hours of intervention time per participant. The second intervention consisted of attending a stress management workshop delivered on 1 day for 4 hours, and no control group was included in the design.…”
Section: Overview Of Specific Psychological and Educational Interventmentioning
confidence: 99%
“…Stress management interventions after an ICD shock were tested by Sears et al 167 One intervention consisted of a CBT stress management intervention delivered by psychologists over 6 weeks in 90-minute sessions, for a total of 9 hours of intervention time per participant. The second intervention consisted of attending a stress management workshop delivered on 1 day for 4 hours, and no control group was included in the design.…”
Section: Overview Of Specific Psychological and Educational Interventmentioning
confidence: 99%
“…53,54 Standard efficacious PTSD treatments are a reasonable starting point for an ICD specific treatment for a postshock stress reaction. 55,56 A promising pilot study revealed success of CBT in a group of patients with myocardial infarction and PTSD symptomatology, which signals support of its applicability with the shocked ICD patient population.…”
Section: Sears Et Al Posttraumatic Stress In Icd Patients 247mentioning
confidence: 99%
“…The most successful strategies for reducing anxiety in ICD patients involve cognitivebehavioral therapy to teach techniques to improve coping skills and illness appraisal, such as developing a shock plan and strategies to reduce negative thoughts. [13][14][15] Other important components of psychological intervention include ICDspecific education, symptom and stress management training, and group therapy. Finally, exercise training as part of a comprehensive cardiac rehabilitation program has reduced anxiety and depression and improved quality of life in ICD patients.…”
Section: Article See P 18mentioning
confidence: 99%